2016
DOI: 10.1161/circresaha.115.308111
|View full text |Cite
|
Sign up to set email alerts
|

CD70 Exacerbates Blood Pressure Elevation and Renal Damage in Response to Repeated Hypertensive Stimuli

Abstract: Rationale Accumulating evidence supports a role of adaptive immunity and particularly T cells in the pathogenesis of hypertension. Formation of memory T cells, which requires the co-stimulatory molecule CD70 on antigen presenting cells, is a cardinal feature of adaptive immunity. Objective To test the hypothesis that CD70 and immunological memory contribute to the blood pressure elevation and renal dysfunction mediated by repeated hypertensive challenges. Methods and Results We imposed repeated hypertensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
106
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(136 citation statements)
references
References 35 publications
3
106
0
Order By: Relevance
“…Production of IFN-γ by CD4 + and CD8 + T cells was recently shown to contribute to BP increase and kidney damage after repeated hypertensive stimuli 17 . Similar to our report in Axl chimeras 15 , we found reduction in arterial expression of IFN-γ (and Th1-dependent pathways) in Axl −/− mice after 6 weeks of DOCA-salt (not shown).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Production of IFN-γ by CD4 + and CD8 + T cells was recently shown to contribute to BP increase and kidney damage after repeated hypertensive stimuli 17 . Similar to our report in Axl chimeras 15 , we found reduction in arterial expression of IFN-γ (and Th1-dependent pathways) in Axl −/− mice after 6 weeks of DOCA-salt (not shown).…”
Section: Resultsmentioning
confidence: 99%
“…Adaptive immune cells such as T lymphocytes contribute to vascular dysfunction and DOCA-salt hypertension 16 . Recent study showed that both CD4 + and CD8 + T cells producing interferon gamma (IFN-γ) are involved in elevation of blood pressure and kidney damage after repeated hypertensive stimuli 17 . Interestingly, the Th1 response in the retina was also shown to be regulated through Axl/Mertk in mice 18 .…”
Section: Introductionmentioning
confidence: 99%
“…After infiltrating these tissues, mononuclear cells release ROS and inflammatory cytokines that regulate tissue injury and alter the release of vasoactive mediators, leading to endothelial dysfunction and/or sodium retention. Ongoing studies continue to parse actions of myeloid and T lymphocyte subpopulations in hypertension, and recent data indicate that distinct pro-inflammatory subsets within these broad populations, for example effector memory T cells, 87, 88 play important roles in blood pressure elevation and consequent target organ damage. By contrast, unique anti-inflammatory immune cell populations, including myeloid-derived suppressor cells and Tregs, can attenuate hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the depletion of DCs prior to I/R injury significantly reduced the kidney levels of TNF-α produced after the injury. In contrast, recent work showed the deleterious action of DCs during kidney injury induced by hypertensive stimuli [61, 62]. These findings suggest that DCs participate in the activation and initiation of immune response and are a key link between innate and adaptive immune responses for myocardial and renal I/R injury.…”
Section: Dcs and Ischemia/perfusion Injury: Potential Link With Typementioning
confidence: 94%